Interacting roles of gut microbiota and T cells in the development of autoimmune hepatitis - Wu, Qingwei; Ge, Zhifa; Lv, Chengyu; He, Qifeng (Frontiers in Immunology, 2025)
Autoimmune hepatitis (AIH) is a progressive liver inflammatory disease mediated by an autoimmune response, with an increasing incidence rate. In severe cases, AIH will rapidly progress to liver cirrhosis and liver failure and even lead to death. The gut microbiota is a complex ecosystem that significantly regulates physiological and pathological processes among various digestive system diseases. It is widely acknowledged that there is a critical correlation between AIH and the gut microbiota. Numerous studies have demonstrated that the composition of gut microbiota in individuals with AIH differs markedly from that of healthy subjects. Immune cells, especially T cells, are pivotal in the development of AIH, closely interacting with the gut microbiota. In this review, we discuss the regulatory role of the gut microbiota in T cell-mediated development of AIH, as well as the effect of T cells on the composition of the gut microbiota in AIH. By modulating gut microbiota or immunity pathways, novel opportunities are provided to regulate the balance of the immune-microbial microenvironment, targeting the dual factor for autoimmune hepatitis therapies.